Integrating conservation agriculture with intensive crop diversification in the maize-based organic system: Impact on sustaining food and nutritional security - Ansari, Meraj Alam; Ravisankar, N.; Ansari, Majhrool Hak; Babu, Subhash; Layek, Jayanta; Panwar, A. S. (Frontiers in Nutrition, 2023)
Developing an intensive sustainable model and feeding a rising population are worldwide challenges. In the Eastern Himalaya, low-productivity maize-fallow is the main agricultural system. To increase system productivity, nutritional security, and energy dietary returns while maintaining environmental sustainability and economic viability, short duration crops must be included into the maize (Zea mays)-fallow system. A field was conducted in sandy clay loam soil a randomized completely block design with three replications for three continuous years (2018-2020) under organic management with two crop management practices viz., (i). Conservation tillage (CT) (ii) conventional agriculture (CA) and six cropping systems viz., (i). maize– sweet corn (Zea mays saccharata)– vegetable pea (Pisum sativa) (CS1) (ii). maize–sweet corn-mustard (Brassica juncea) (CS2) (iii). maize-sweet corn-lentil (Lens culinaris) (CS3) (iv). maize-sweet corn- vegetable broadbean (Vicia faba) (CS4) (v). maize (Local) – vegetable pea (CS5) and (iv). maize local as farmers practice (CS6). Over three years of experimentation, the average system productivity was 5.3% lower for conventional agriculture than conservation tillage. System carbohydrate, protein, fat, dietary fibre and dietary energy were about 6.9%, 6.8%, 7.8%, 6.7% and 7% respectively, higher under conservation tillage than conventional agriculture. Similarly, system macro nutrients (Ca, Mg, P and K) and system micronutrients yield (Fe, Mn, Zn and Cu) respectively, 5.2-8% and 6.9-7.4% higher in conservation tillage than conventional agriculture. The average over the years, maize-sweet corn-vegetable pea/broadbean intensive crop rotation had higher system productivity (158%), production efficiency (157%), net returns (171.5%), benefit cost ratio (44%) and dietary net energy returns (16.6%) than the predominantly practiced local maize -vegetable pea crop rotation. Similarly, maize-sweet corn-vegetable pea/broadbean system improved the nutritional security by improving Ca, Mg, P, K, Fe, Mn, Zn and Cu yield by 35.5-135.7% than local maize -vegetable pea system. Conservation tillage with maize-sweet corn-vegetable pea/broadbean rotation showed significantly (p<0.05) higher productivity, carbohydrate yield, protein yield, fat yield, and dietary fibre production. It is concluded that conservation tillage performed better than conventional agriculture in maize based intensive cropping systems. Our results indicate that intensive maize-based cropping systems may increase calorie and protein consumption and farm profitability.